The Influence of Product Quality and Brand Image with the Moderation of Customer Satisfaction on Customer Retention of iPhone Smartphone Users (Case Study in Sukabumi Regency) - Yuliana, Rena; Prihasti N, Ressa (Westscience Press, 2024)
This study aims to analyze the influence of product quality and brand image with customer satisfaction moderation on customer retention of iPhone smartphone users in Sukabumi Regency. The background of this study is based on the importance of understanding the factors that influence customer loyalty in the highly competitive smartphone industry. This study uses a quantitative research method. The population in this study is iPhone smartphone users who live in Sukabumi Regency. The number of samples taken was 155 people, with non-probability sampling used to determine the sample. The data used in this study is primary data, namely by distributing questionnaires. The measurement scale used is the Likert scale. The statistical method used is Partial Least Square (PLS) and the data analysis technique uses the SmartPLS version 3.0 program. The results of the study show that product quality and brand image have a positive and significant effect on customer retention. However, customer satisfaction does not positively moderate the relationship between product quality and brand image with customer retention. Further research is recommended to explore other factors that can moderate this relationship.